The preparation of cordierite-mullite composite for thermal shock resistance material - Kiattisaksophon P. (2014)
In this study aims to prepare cordierite-mullite composite to be use as a thermal shock resistance materials. Commercial available cordierite and mullite powders were used as starting raw materials with various ratios up to 100 wt% and were mixed together by ball milling in order to prepare a composite material. 0.6 wt% polyvinyl alcohol (PVA) was also added in the mixtures. The specimen was pressed under 1,500 kg/cm2 and sintered between 1250°C and 1400°C with a temperature interval of 50°C. The thermal expansion coefficient was measured and observed by loop of thermal behavior when heated up to maximum temperature and cooled down to room temperature. Thermal behavior was studied. Thermal shock resistance was measured following ASTM method. The microstructure of composite has been characterized by scanning electron microscope (SEM). The result revealed that the percentage of cordierite-mullite at 70:30 wt% and sintered at 1400 °C showed good results in both of physical and thermal properties.